White matter microstructure correlates of age, sex, handedness and motor ability in a population-based sample of 3031 school-age children - Mónica López-Vicente; Sander Lamballais; Suzanne Louwen; Manon Hillegers; Henning Tiemeier; Ryan L. Muetzel; Tonya White (NeuroImage, 2021)
Understanding the development of white matter microstructure in the general population is an imperative precursor to identifying its involvement in psychopathology. Previous studies have reported changes in white matter microstructure associated with age and different developmental patterns between boys and girls. Handedness has also been related to white matter in adults. Motor performance, tightly dependent on overall neuronal myelination, has been related to the corpus callosum. However, the association between motor performance and global white matter microstructure has not been reported in the literature. In general, these age, sex, handedness, and motor performance associations have been observed using small and poorly representative samples. We examined the relationships between age, sex, handedness, and motor performance, measured with a finger tapping task, and white matter microstructure in the forceps major and minor and in 5 tracts bilaterally (cingulum, corticospinal, inferior and superior longitudinal fasciculi, and uncinate) in a population-based sample of 3031 children between 8 and 12 years of age. Diffusion tensor imaging (DTI) data were acquired using a single, study-dedicated 3 Tesla scanner. We extracted and quantified features of white matter microstructure for each tract. We computed global DTI metrics by combining scalar values across multiple tracts into single latent factors using a confirmatory factor analysis. The adjusted linear regression models indicated that age was associated with global fractional anisotropy (FA), global mean diffusivity (MD), and almost all the tracts. Further, girls showed lower global MD than boys, while FA values differed by tract, and no age-sex interactions were found. No differences were observed in white matter microstructure between right- and left-handed children. We observed that FA in forceps major was associated with right-hand finger tapping performance. White matter FA in association tracts was only related to motor function before multiple testing correction. Our findings do not provide evidence for a relationship between finger tapping task performance and global white matter microstructure.